Visual rhetoric : An alternative method of designing Luoshan shadow creative products - Taotao, Xu; Musdi, Shanat (Silpakorn University, Thailand, 2024)
The Luoshan shadow puppet, which has a long history in China, is a multifaceted art form incorporating carving, performance, and painting. This art has also resulted in the production of numerous creative products. In the digital information age, visual symbols play an increasingly important rhetorical role in the Luoshan shadow creative products. The Luoshan shadow creative products have been designed to combine traditional cultural elements with modern aesthetics practically and artistically. This paper aims to investigate how visual rhetoric influences design innovation in the Luoshan shadow creative products and explain how it is used to design these creative products. A thematic analysis of comments and suggestions from 16 designers and academics was carried out, and a framework of roles and strategies for visual rhetoric to influence the Luoshan shadow creative product was suggested. The proposed framework incorporates a visual rhetorical approach and shows how it influences creative product designs. The exploration in this study adheres to a visual rhetorical model, with these approaches classified into four levels of innovation: innovative visual thinking, new visual connections, form following emotion, and formal restructuring to improve visual appeal. The framework also shows how the connection and overlap of visual rhetorical approaches contribute to how these products innovate and create new visual meanings.